Effects of transformational leadership of head coach and leadership substitute variables on assistant coach job satisfication in Thailand - Taweesuk, Duangkrai (2011)
The purpose of this research was to determine the influence of transformational leadership behavior of head coaches and leadership substitute variables as determinants of assistant coaches’ job satisfaction in Thailand. Questionnaires were given to 250 Thai assistant coaches in 30 sports. The questionnaire consists of the Transformational Leadership Inventory (TLI) developed by Podsakoff,et al., (1990), Leadership Substitutes Questionnaire (LSQ) developed by Kerr and Jemier, (1978) and the Job Satisfaction Survey (JSS) developed by Spector (1994). Study showed that there was a significant relationship between assistant coaches' perception of their head coaches' transformational leadership behavior and assistant coaches’ job satisfaction. There is no significant relationship between leadership substitute variables and job satisfaction of assistant coaches. The results also showed a positive relationship between Unambiguous Routine and Methodologically Invariant Tasks, Organizational Formalization, Advisory and Staff Functions, and Organizational Rewards not within the Leaders’ control and assistant coaches’ job satisfaction. There was a negative relationship between Ability Experience Training and Knowledge, Professional Orientation, Indifference toward Organizational Rewards, and Task Provided feedback Concerning Accomplishments and assistant coaches’ job satisfaction. Spatial distance between superior and subordinates was discovered to be leadership enhancers, while intrinsically satisfying tasks to be a neutralizer of transformational leadership behaviours in Thailand. It was concluded that transformational leadership behaviours of head coaches have a direct relationship with assistant coaches’ job satisfaction in the absence of a strong leadership enhancer or neutralizer. However, in the presence of leadership enhancer and neutralizer, it was concluded that transformational leadership behaviours of head coaches influenced assistant coaches’job satisfaction indirectly, through the moderating effects of the enhancers and neutralizer.